PENGARUH PELAYANAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT DI SUMATERA BARAT - Sasnelwati, Sasnelwati (Jurnal Ekobistek, 2015)
The impact of service quality on patient satisfaction in hospital at West Sumatera.Then the collection of analytical methods is with t count> t table (5.816> 1.661) with asignificant level of 0.000 <0.05, which means that the partial was no significant effect betweenTangible with patient satisfaction. with t count> t table (10,079> 1.661) with a significant levelof 0.000 <0.05, which means that the partial was no significant effect between Empahy withpatient satisfaction. with t count> t table (11,399> 1.661) with a significant level of 0.000 <0.05,which means that the partial was no significant effect between Reliability with patientsatisfaction. with t count> t table (12,910> 1.1661) with a significant level of 0.000 <0.05,which means that the partial was no significant effect between Responsivenees with patientsatisfaction. with t count> t table (13,627> 1.661) with a significant level of 0.000 <0.05,meaning that there are partially significant influence Assurance with patient satisfaction. Thereis positive and significant correlation between Tangible, Empathy, Reliability, Responsivenessand Assurance. From the results of the test with SPSS 15.0 for window obtained calculated Fvalue of 47,025 with the F table at 2,311 with this significant 0.000 <0.05. This means that thereis significant influence between Tangible, Empathy, Reliability, Responsiveness and Assurancejointly influence on patient satisfaction. So from this case can be concluded that betweenTangible, Empathy, Reliability, Responsiveness and Assurance jointly influence the PatientSatisfaction Hospital at West Sumatera.Finally, the author suggests the Hospital should further improve the quality of carebecause of the research that the quality of service has an influence on patient satisfaction inHospital at West Sumatera. The research result shows that the variable Tangible ¸ Empathy,Reliability, Responsiveness , Assurance, can be improved so that higher patient satisfactionsuch as: reliable products, quality services more responsive, Staff must do the work in aconsistent, accurate, and reliable. And from the study showed that the variables ¸ TangibleEmpathy, Reliability, Responsiveness and Assurance has an influence on patient satisfaction ..However, the hospital should not be easily satisfied for what has been achieved at WestSumatera Hospital and should pay more attention to facilities and showed genuine concern forhis patients in order to create a sense of satisfaction and accompanied with products offeredagain.Keyword: Tanggible, Empathy, Realibility, Responsiveness, Assurance, Petientsatisfaction.